An Assembly + Ensemble x.y: Leung, Miller, Harrison, Finnissy. St John's Waterloo, London. (6th September 2018) - Barry, Robert
Abstract : 'Gently rumbling without direction', a programme note appended to the first part of Cassandra Miller's solo for piano Philip the Wanderer, might equally have stood in as descriptor for tonight's programme tout court . This is not meant as a criticism. Time's arrow, the vector of narratives real or implied, may well be the most burdensome yet most easily sloughed off (and perhaps least missed) item of nineteenth-century baggage to be jettisoned by composers over the last century or so. What tonight's collaboration between An Assembly and Ensemble x.y (led and programmed by the increasingly omnipresent wunderkind of British new music, Jack Sheen) offered up was a quite different approach, a different way through the passage of time. Less music as organised sound; more sound in itself a means for organising time.